(untitled) (Applied Biological Research, 2015)
Effect of graded doses of chlorpyrifos on haemato-biochemical indices in broiler chickens was investigated. A total of 72 broiler chickens, 3 week old, were divided into four groups (I to IV) consisting of 18 birds each. Group I served as control, whereas groups II, III and IV received 3.2, 1.6 and 0.6 mg kg-1 B.W. chlorpyrifos in corn oil daily for 6 weeks. Blood samples were collected in sterile vials containing EDTA (@ 1 mg mL-1) as anticoagulant for haematological studies and without anticoagulant for biochemical parameters. Mean values of Hb, PCV, TEC, MCV, MCH, MCHC, TLC and lymphocyte counts decreased significantly in all the treatment groups, whereas platelet count increased significantly. Serum total protein, albumin and A:G ratio showed decrease, whereas serum ALT, AST, RBC acetyl cholinesterase and butryl-cholinesterase activities exhibited increase. The study revealed that chlorpyriphos has haemotoxic, immune-toxic, hepatotoxic, nephrotoxic and neurotoxic effects in broiler chickens.